A non-human primate model of acute liver failure suitable for testing liver support systems - Kalsi, Ranjeet S.; Ostrowska, Alina; Olson, Adam; Quader, Mubina; Deutsch, Melvin; Arbujas-Silva, Norma J.; Symmonds, Jen; Soto-Gutierrez, Alejandro; Crowley, John J.; Reyes-Mugica, Miguel; Sanchez-Guerrero, Giselle; Jaeschke, Hartmut; et al. (Frontiers in Medicine, 2022)
Acute hepatic failure is associated with high morbidity and mortality for which the only definitive therapy is liver transplantation. Some fraction of those who undergo emergency transplantation have been shown to recover native liver function when transplanted with an auxiliary hepatic graft that leaves part of the native liver intact. Thus, transplantation could have been averted with the development and use of some form of hepatic support. The costs of developing and testing liver support systems could be dramatically reduced by the availability of a reliable large animal model of hepatic failure with a large therapeutic window that allows the assessment of efficacy and timing of intervention. Non-lethal forms of hepatic injury were examined in combination with liver-directed radiation in non-human primates to develop a model of acute hepatic failure that mimics the human condition. Porcine hepatocyte transplantation was then tested as a potential therapy for acute hepatic failure. After liver-directed radiation therapy, delivery of a non-lethal hepatic ischemia-reperfusion injury reliably and rapidly generated liver failure providing conditions that can enable pre-clinical testing of liver support or replacement therapies. Unfortunately, in preliminary studies, low hepatocyte engraftment and over-immune suppression interfered with the ability to assess the efficacy of transplanted porcine hepatocytes in the model. A model of acute liver failure in non-human primates was created that recapitulates the pathophysiology and pathology of the clinical condition, does so with reasonably predictable kinetics, and results in 100% mortality. The model allowed preliminary testing of xenogeneic hepatocyte transplantation as a potential therapy.